The illustrated guide to God : an A to Z encyclopedia of his names, attributes, and role in the world - Knight, George W. (Barbour Publishing Inc, 2014)
If you want to understand God better, read "The Illustrated Guide to God--An A to Z Encyclopedia of His Names, Attributes, and Role in the World." This brand-new reference from George W. Knight--author of the popular "Layman's Bible Dictionary" and "The Holy Land: An Illustrated Guide--"contains nearly 600 entries on the names of God, Jesus, and the Holy Spirit; characteristics of God, such as His eternity, jealousy, and omniscience; key people and places in God's biblical history, from Aaron to Zion; and important theological concepts, including apostasy, regeneration, and worship. Illustrated with beautiful, full-color artwork, and containing hundreds of cross-references, "The Illustrated Guide to God" is ideal both for fascinating reading and serious Bible study.